Delayed Concurrent Chylothorax and Chyloperitoneum: Report of a Case after an Old Blunt Trauma - Sokouti, Mohsen (National Research Institute of Tuberculosis and Lung Disease, 2011)
A 15- year-old boy was referred to Imam Reza Hospital with a right chest tube and chylothorax for 40 days. The patient had respiratory distress and undergone refractory treatment for chylothorax. The fluid content was chyle-rich in lipids. Computed Tomography of the chest showed a large, incompletely evacuated cyst in the left posterior mediastinum with left pleural effusion. The cyst could not be resected through right thoracotomy, because of the left side location of the cyst. Ligation of the thoracic duct through right thoracotomy was not effective in reducing chylous effusion 4 days later. Left chylothorax exacerbated because of the complication of right thoracotomy. Laparatomy was performed to ligate the thoracic duct 6 days later. On exploratory laparatomy, chylous effusion was detected in the peritoneum. Thoracic duct with all the fibro-fatty tissues was ligated below the diaphragm over the spine at 12(th) to 2(nd) vertebral spaces. Right chylothorax was resolved after ligation of thoracic duct transabdominally 1-2 days later. Left chylous effusion was decreased and treated 46 days after laparatomy. One year follow up of the patient showed excellent result. In our knowledge, thoracic duct cyst occurring as a result of a delayed chylothorax and chyloperitoneum has not been reported in the literature. Surgical thoracic duct ligation can be the treatment of choice.